Novel fractal geometry of 4×4 multi-input and multi-output array antenna for 6G wireless systems - Karrar Shakir Muttair; Oras Ahmed Shareef; Hazeem Baqir Taher (Universitas Ahmad Dahlan, 2024)
Recently, multiport multi-input and multi-output (MIMO) antenna technology has been the main focus of both manufacturers and researchers. So, their biggest challenge was to propose a small antenna that operates in broadband. We will be the primary contributors to the manufacturing process for this sort of antenna in this work, so we suggested a 4×4 MIMO antenna in a very compact size. As a result, the antenna dimensions are (W=16 mm, L=16 mm, H=1.6 mm) and it operates in millimeter bands ranging from 38 to 80 GHz, with a wide bandwidth of 42 GHz. This antenna was created using modern design principles, such as the Rubik’s cube form. According to the results, we noticed that the performance of the parameters is good, as the reflection coefficient is <10 dB for all frequencies. In addition, the isolation transmission performance between ports is <-26 dB, the envelope correlation coefficient (ECC) is <0.0000234 between all ports, and the diversity gain (DG) ranges between ports from 9.99 to 10 dB. Moreover, the percentage of the total antenna efficiency and radiation ranges from 70 to 98%, while the projected antenna gain range from 6.9 to 9.5 dB. With all these positive results, the suggested antenna has become one of the critical components in most contemporary wireless systems.